Learning the notion of learning goal in an initial functional training program (2008)
In an initial functional teacher-training program, future teachers are expected to develop their competences for using mathematics education notions in order to analyze a mathematics school concept and use the information emerging from such analysis for the design and implementation of didactic units. In this paper we propose a set of conceptual and methodological tools for exploring and characterizing future teachers learning of those notions. These tools are based on the ideas of meaning, technical use, and practical use of a notion. We exemplify the use of these tools for the case of the notion of learning goal.